A atuação da ONG amazona – Associação de prevenção à AIDS junto á comunidade São Rafael: o (des) fazer juntos à luz da educação em direitos humanos - Machado, Viviane Alves (2017)
The perspective of this Master's Dissertation – The role of AMAZONA - Associação de Prevenção à AIDS NGO in the São Rafael Community: (un) doing together in the light of human rights education – is to understand the insertion of non-formal education and Human Rights in the practice of these two organizations, Amazona NGO and the CPCC – Centro Popular de Cultura e Comunicação, with the young public. The General Objective of this study is to analyze the role of Amazona NGO towards the formation of youth leaderships in the community of São Rafael, in the light of Human Rights Education - HRE. Its specific objectives are: to identify and evaluate the initiatives of non-formal education in Human Rights, developed by Amazona NGO with the adolescents and young people of the São Rafael community; To investigate how a community organization led by young people, CPCC, was created, based on the activities of Amazona NGO; Configure the profile of these young people as well as the mission of the organization; Understand the motivations of these young people on developing community work; Analyze the meanings of HRE internalized by young people, educators, trainers and managers, as a practice of Amazona and CPCC. The methodological framework for this investigation is qualitative research of an exploratory and descriptive character, starting from the bibliographical survey and the literature review of the academic production on the subject; Documentary and empirical insertions, involving interviews and a focus group with young community leaders who work with the CPCC. Thus, this research intends to offer theoretical and practical contributions to the work of the Social Organizations (Amazona and CPCC), pointing out their pedagogical actions and the contents that enable the formation of youth and of young leaders and the relation of these actions with Education in Human Rights, which were and are built through the needs present in the social reality of the community.